Sports and understanding organizations - Svyantek, Daniel J. (Emerald Publishing Limited : IAP, Information Age Publishing, INC., 2017)
This volume provides readers with a rich source of sports metaphors for understanding organization and management processes and how to use metaphors to become more effective leaders and managers within their organizations. Each chapter discusses how sports may be used to help improved organizational productivity and effectiveness.These chapters each strive to present new ways of understanding organizational constructs using sports as a metaphor. It is this volume's hope that these chapters may provide insight into the important role sports plays in understanding organizations across the world. Organizational science profits from taking new perspectives that may be found when sports is used as a lens for this study.
Keywords: Sports administration -- United States.; Sports -- United States -- Management.; Sports -- Social aspects.; Sports & Recreation -- General.; Sport: general.; elektronické knihy; electronic books